CURRENT DIRECTIONS OF PROFESSIONAL TRAINING OF FUTURE MASTERS IN PRE-SCHOOL EDUCATION FOR THE ORGANIZATION OF CHILDREN’S ENVIRONMENTAL ACTIVITIES IN PRESCHOOL EDUCATION INSTITUTIONS OF UKRAINE - Lysenko, Nelli; Lysenko, Olexandra; Matishak, Marianna; Skomorovska, Iryna (Mountain School of Ukrainian Carpaty, 2022)
The article analyzes the peculiarities of professional training of future teachers for the organization of proenvironmental education of preschool children in modern preschool education institutions. It was emphasized that the content of such training should be based on the provisions of regulatory documents, taking into account the requirements of the Basic Component of Preschool Education (State Standard of Preschool Education), which contains the content and key requirements for the formation of preschool children's natural and ecological competence and skills focused on sustainable development. It has been established that the ecological education of children in the process of their familiarization with the natural environment should be aimed at raising a conscious, responsible and caring attitude towards the natural environment and all possible forms of existence of its objects. The ultimate goal of environmental education is the formation of environmental awareness and ecological culture. Operational goals of pro-ecological education of preschool children are presented in separate blocks: creation of conditions for children to search for information of natural and ecological content; acquainting children with adults' views on nature; formation of children's ability to observe changes in the natural environment, skills of careful attitude to the natural environment, economical consumption of resources and nature conservation; forming in adults a sense of moral responsibility for the state of the natural and social environment and a careful attitude towards the nature of the native land in general. In the context of the effective training of masters in preschool education for environmental activities with preschool children, the characteristics of the foundations of pro-ekological consciousness of preschool children were revealed, namely: the ability to learn about the phenomena of the social and natural environment; interest in learning about the world around and the phenomena that occur in it; awareness and understanding of the rules that exist in nature; responsibility for various forms of life on Earth; activity and awareness of the feeling of mutual indivisibility between nature and people; the need to protect and respect the natural environment.